2022
DOI: 10.1038/s41598-022-24643-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower SARS-CoV-2 household transmission in children and adolescents compared to adults

Abstract: In the COVID-19 pandemic, children were considered to play a major role in SARS-CoV-2 transmission similar to influenza. Thus, mitigation measures have been focused on children, impacting their everyday life severely. Despite this, infectivity in this age group regarding SARS-CoV-2 is not yet clarified. We performed a serology study in households with confirmed SARS-CoV-2 infection to evaluate virus transmission with focus on children and adolescents. Between January and July 2021, 341 minors and 650 adults fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These findings were echoed in studies outside of households where the infection rate of SARS-CoV-2 among children younger than 10 years was significantly lower than that of adults [2]. However, since August 2020, the continuous emergence of new variants of SARS-CoV-2 has raised questions as to whether there has been a fundamental shift in the epidemiology of SARS-CoV-2 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were echoed in studies outside of households where the infection rate of SARS-CoV-2 among children younger than 10 years was significantly lower than that of adults [2]. However, since August 2020, the continuous emergence of new variants of SARS-CoV-2 has raised questions as to whether there has been a fundamental shift in the epidemiology of SARS-CoV-2 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the associated risks of anesthesia complications and exposure for perioperative staff and patients, many elective surgeries have been postponed or canceled. Compared to adults, a higher proportion of pediatric patients infected with the novel coronavirus exhibit asymptomatic infections, and their infectivity is significantly lower than that of adult patients [ 1 ]. Omicron rapidly replaced Delta as the dominant variant worldwide since November/December 2021 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about whether the role of children in familial clusters has changed with the rollout of vaccination and the emergence of variants of concern (VOC). A study during the VOC Beta wave in Germany found that household transmission from adults was more frequent than from children [4]. Furthermore, as most studies evaluating the direction of transmission took place in high-income countries, little is known about the direction of transmission between age groups in lower resource settings.…”
mentioning
confidence: 99%